2017
DOI: 10.1093/heapro/dax069
|View full text |Cite
|
Sign up to set email alerts
|

Late booking amongst African women in a London borough, England: implications for health promotion

Abstract: The National Institute for Health and Clinical Excellence guidance is that a pregnant woman should see a midwife within the first 13 weeks into her pregnancy, in what is known as the 'booking appointment' or the 'full assessment' where she discusses with the midwife her care plan, medical and family histories and social circumstances. Significant numbers of black African women present after 13 weeks into the pregnancy. This study explores why black African women access the booking appointment after 13 weeks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…There is little qualitative research on the lived experiences of all ethnic minority women during or immediately following pregnancy in the UK. Previous qualitative literature in the UK has tended to focus on nuanced aspects of maternal care, 15 particular health conditions during pregnancy 16 or specific ethnic groups. 17 This study aimed to explore the experiences of pregnancy, childbirth, antenatal and postnatal care in all women belonging to ethnic minority communities and to identify any specific challenges that these women faced during the SARS-CoV-2 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…There is little qualitative research on the lived experiences of all ethnic minority women during or immediately following pregnancy in the UK. Previous qualitative literature in the UK has tended to focus on nuanced aspects of maternal care, 15 particular health conditions during pregnancy 16 or specific ethnic groups. 17 This study aimed to explore the experiences of pregnancy, childbirth, antenatal and postnatal care in all women belonging to ethnic minority communities and to identify any specific challenges that these women faced during the SARS-CoV-2 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has revealed high prevalence but low awareness of cardiometabolic disease among African immigrants in the U.S. [8,9]. Other studies of African immigrants living in high-income settings have found low levels of health insurance [10] and linkage to primary care [11,12] as well as low or delayed uptake of vaccination [13,14], cancer screening [15,16], antenatal care [17], and diabetes screening [18]. Therefore, identifying and addressing specific barriers to engagement in preventive health care (defined here as proactive measures taken to prevent or mitigate future illness) is needed to improve health outcomes of African immigrant populations in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…This propels the argument that IK is deeply embedded in a society's cultural values and practices. As postulated by Chinouya and Madziva (2017), culture is often a crucial determinant of reproductive health behaviors including those relating to accessing antenatal care within the timeframes prescribed by clinicians, namely 12 weeks into the pregnancy. Helman (1984, p. 3) defines culture as "a set of guidelines (explicit and implicit) which an individual inherits as a member of society, and which tells him how to view the world and how to behave in it in relation to other people, to supernatural forces or gods and the environment.…”
Section: Theoretical Framework: a Cultural Practice Embedded In Indigmentioning
confidence: 99%